2020
DOI: 10.3389/fcimb.2020.00442
|View full text |Cite
|
Sign up to set email alerts
|

Serum From Melioidosis Survivors Diminished Intracellular Burkholderia pseudomallei Growth in Macrophages: A Brief Research Report

Abstract: Melioidosis is a neglected tropical disease with high mortality rate. It is caused by the Gram-negative, CDC category B select agent Burkholderia pseudomallei ( B. ps ) that is intrinsically resistant to first-line antibiotics. An antibody-based vaccine is likely to be the most effective control measure. Previous studies have demonstrated significant mechanistic roles of antibodies in protection against death in animal models, but data from human melioidosis is sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…Our ADCP results in this study confirmed findings from a previous report by Chaichana et al that serum from melioidosis patients can enhance opsonization of B. pseudomallei in a THP-1 cell derived macrophage model ( 25 ). Although a follow-up study by Chaichana et al demonstrated that high levels of total IgG2 and the expression of FcγRIIa-H/R131, an intermediate-affinity IgG2 receptor, were associated with protection against death in acute melioidosis ( 26 ), they did not identify the specific target antigen for IgG2 as they used whole cells of B. pseudomallei in their assay.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our ADCP results in this study confirmed findings from a previous report by Chaichana et al that serum from melioidosis patients can enhance opsonization of B. pseudomallei in a THP-1 cell derived macrophage model ( 25 ). Although a follow-up study by Chaichana et al demonstrated that high levels of total IgG2 and the expression of FcγRIIa-H/R131, an intermediate-affinity IgG2 receptor, were associated with protection against death in acute melioidosis ( 26 ), they did not identify the specific target antigen for IgG2 as they used whole cells of B. pseudomallei in their assay.…”
Section: Discussionsupporting
confidence: 92%
“…A study in human melioidosis showed a lower mortality rate was associated with seropositivity against crude B. pseudomallei antigen preparations ( 23 ). We previously reported an association of survival with high levels of IgG against OPS and Hcp1 in melioidosis patients ( 18 , 24 ) suggesting a potential functional role for these antibodies in protection against disease ( 25 ). In addition, Chaichana et al demonstrated that serum from survivors of melioidosis enhanced bacterial uptake compared to serum from nonsurvivors ( 25 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum antibodies against B. pseudomallei cell surface polysaccharides and proteins are detectable in acute melioidosis infections (26,28,(42)(43)(44). There is some evidence in human and animal models that antibody responses play a key role in protection against melioidosis (14,15,26,31,45,46). Our previous studies showed that melioidosis patients who lived in endemic areas had high IgG responses to Hcp1 and Opolysaccharide (28,31,47).…”
Section: Discussionmentioning
confidence: 99%
“…Bukholderia pseudomallei is a soil and water surface bacterium found in tropical areas that causes melioidosis after exposure to contaminated water or soils [114]. Melioidosis has been reported in Malaysia and other endemic countries such as Brazil [124], Australia [125], India [126] and Thailand [127]. Infection with B. pseudomallei is most commonly associated with an inoculating injury, ingestion, or inhalation of aerosolized bacteria and occurs more frequently in the wet season or following extreme weather events such as tropical storms.…”
Section: Melioidosismentioning
confidence: 99%